Jahresbericht des Vereins Kunsthalle Bern 1994. - Hahnloser, Bernhard; Loock, Ulrich; Kunsthalle Bern (Bern : Kunsthalle Bern, 1995)
Zitko, Otto ; Gritsch, Stefan ; Lanz, Eric ; Schubiger, Irene ; Streuli, Beat ; Tison, Nathalie ; Tusek, Mitja ; Voïta, Bernard ; Bustamante, Jean-Marc ; Ray, Charles ; Zobernig, Heimo ; etc.
Duits
boek